Exome sequencing and functional studies in zebrafish identify WDR8 as the causative gene for isolated Microspherophakia in Indian families. Issue 6 (9th March 2021) - Madhangi, M; Dutta, Debanjan; Show, Sautan; Bhat, Vishwanath K; Rather, Mohammad I; Tiwari, Ankana; Singh, Nivedita; Duvvari, Maheswara R; Murthy, Gowri J; Kumar, Arun; Nongthomba, Upendra
Abstract: Isolated Microspherophakia (MSP) is an autosomal recessive disorder characterized by a smaller than normal spherical lens. Till date, LTBP2 is the only gene shown to cause MSP. We used homozygosity mapping and whole-exome sequencing and identified a homozygous mutation, c.1148C > T (p.Pro383Leu), in the WDR8 (or WRAP73) gene in two Indian MSP families. In vitro experiments showed that the missense mutation renders the protein unstable. WDR8 is a centriolar protein that has important roles in centrosomal assembly, spindle pole formation and ciliogenesis. Co-immunoprecipitation experiments from HeLa cells indicated that the mutation interferes with the interaction of WDR8 with its binding partners. In zebrafish, both morpholino-mediated knockdown and CRISPR/Cas knockout of wdr8 resulted in decreased eye and lens size. The lack of wdr8 affected cell cycle progression in the retinal cells, causing a reduction in cell numbers in the retina and lens. The reduction in eye size and the cell cycle defects were rescued by exogenous expression of the human wild-type WDR8. However, the human mutant WDR8 (p.Pro383Leu) was unable to rescue the eye defects, indicating that the missense mutation abrogates WDR8 protein function. Thus, our zebrafish results suggested that WDR8 is the causative gene for MSP in these Indian families. Graphical abstract: